Evaluation of PCMH Model Adoption on Teamwork and Impact on Patient Access and Safety - Niharika Khanna; Fadia T. Shaya; Priyanka Gaitonde; Andrea Abiamiri; Ben Steffen; David Sharp (SAGE Publishing, 2017)
Purpose: Each of the participating patient-centered medical home (PCMH) received coaching and participated in learning collaborative for improving teamwork. The objective of the study was to assess the impact of trainings on patient-centered teamwork. Methods: The Teamwork Perception Questionnaire (TPQ) was administered once in spring 2014 and then in fall 2015. The TPQ consists of 35 questions across 5 domains: mutual support, situation monitoring, communication, team structure, and leadership. Based on our objective we compared the frequencies of strongly agree/agree by domain. The difference was tested using chi-square test. We compared the scores on each domain (strongly agree/agree = 1; maximum score = 7) via Wilcoxon rank sum test. Results: The response rate for this survey was n = 29 (80.6%) in spring 2014, and n = 31 (86.1%) in fall 2015. We found that the practice members significantly ( P < .05) strongly agreed/agreed more in fall 2015 than spring 2014 for characteristics-"staff relay relevant information in a timely manner" (64.5% vs 83.9%) and "staff follow a standardized method of sharing information when handing off patients" (67.7% vs 90.3%) under communication domain and for characteristic-"staff within my practice share information that enables timely decision making" (74.2% vs 90.3%). However, there was no statistical significant difference observed in the scores for the overall TPQ at the 2 time points. Conclusion: Despite the statistical insignificance, the observations in PCMHs across the spectrum of practices participating in the Maryland Multi-Payer Program demonstrated enhanced teamwork specifically in communication and in leadership. This we believe will continue to result in enhanced patient access to care and safety.